Shear strength enhancement of fine sand soil using Guar Gum biopolymer under varying curing conditions - Riza Suwondo; Maya Devina Kurniawan; I Gede Mahardika Susila; Andryan Suhendra (Universitas Mercu Buana, 2026)
This study investigates the effect of Guar Gum biopolymer on the shear strength behaviour of fine sand soil, with the aim of evaluating its potential as a sustainable soil stabilization agent. A series of direct shear tests, following ASTM D3080-23, was conducted on Guar Gum-treated soil samples with varying biopolymer concentrations (1%, 3%, and 5%) and water content (10%, 12%, and 15%). Curing durations of 2, 5, and 7 days were applied to assess time-dependent strength development. The shear strength parameters, cohesion (c) and internal friction angle (φ), were evaluated to quantify the improvement in soil performance. The results showed that cohesion increased with higher Guar Gum concentration and longer curing times, with the highest cohesion (0.105 kg/cm²) observed at 5% concentration after 7 days. However, the internal friction angle decreased with prolonged curing, suggesting a shift from the frictional to cohesive strength. Water content had a significant impact, with 10–12% yielding optimal results. At a water content of 12 %, the highest internal friction angle (52°) was recorded after 7 days. Overall, the findings confirm that Guar Gum can significantly enhance the shear strength of fine sand when key parameters are optimized, offering an effective, environmentally friendly alternative to conventional chemical stabilizers in geotechnical applications.